2013
DOI: 10.1212/wnl.0b013e318281cc43
|View full text |Cite
|
Sign up to set email alerts
|

Functional disturbance of the locomotor network in progressive supranuclear palsy

Abstract: Gait impairment in PSP is especially associated with dysfunction of the indirect, modulatory prefrontal-subthalamic-pedunculopontine loop of locomotor control. The direct, stereotyped locomotor loop from the primary motor cortex to the spinal cord with rhythmic cerebellar drive shows increased activity in PSP. The latter can be interpreted as an attempt of compensation, but may also contribute to a stereotyped gait pattern in PSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 39 publications
4
60
0
Order By: Relevance
“…This also agrees with a study which demonstrated that the post-erolateral thalamus was involved in resistance to the Aubert effect, i.e., the deviation of visual vertical estimates in the direction of body tilts [20]. Furthermore, an association of postural instability and falls with thalamic dysfunction has been demonstrated in PSP-Richardson phenotype with prominent postural instability [31,40]. In our study, a pronounced backward deviation of the SBV correlated with greater ventricular enlargement.…”
Section: Mechanisms Underlying Postural Instability In the Pitch Plansupporting
confidence: 93%
“…This also agrees with a study which demonstrated that the post-erolateral thalamus was involved in resistance to the Aubert effect, i.e., the deviation of visual vertical estimates in the direction of body tilts [20]. Furthermore, an association of postural instability and falls with thalamic dysfunction has been demonstrated in PSP-Richardson phenotype with prominent postural instability [31,40]. In our study, a pronounced backward deviation of the SBV correlated with greater ventricular enlargement.…”
Section: Mechanisms Underlying Postural Instability In the Pitch Plansupporting
confidence: 93%
“…The complexity of additional simultaneous cognitive tasks probably has a considerable impact on walking performance and brain activity as indicated by studies summarized in our current review (Beurskens et al, 2014;Hill et al, 2013) as well as in other non-included work (Al-Yahya et al, 2011;Hall et al, 2011;Patel et al, 2014;Srygley et al, 2009). However, patients with neurological pathologies seem to either compensate their structural and/or functional impairments by an augmented activation of brain areas or by recruiting additional brain areas (Cremers et al, 2012;Jahn et al, 2009;Peterson et al, 2014a;Peterson et al, 2014b;Snijders et al, 2011;Wai et al, 2012;Zwergal et al, 2013).…”
Section: Complex Motor Tasks Dual Tasks and Speedmentioning
confidence: 50%
“…primary sensorimotor cortex Ouchi et al (2001) 1. healthy subjects (n= 6 / 65.3 ± 5.9) / Parkinson patients (n = 7 / 66.3 ± 6.6) 2. [ ] -CFT -PET Healthy subjects / Walking (vs rest): significant reduction of marker substance in putamen and caudate (indicate higher brain activity) PD patients / walking (vs. rest): significant reduction of marker substance in orbitofrontal cortex and caudate (indicate higher brain activity) PD patients vs. healthy controls / walking: no significant group differences in gait orbitofrontal [ ] -CFT uptake was inversely correlated with cadence ROI = caudate, putamen, orbitofrontal cortex and cerebellum Zwergal et al (2013) PSP A c c e p t e d M a n u s c r i p 52 Page 54 of 57 A c c e p t e d M a n u s c r i p 54 Table 9: Brain activity during different walking speeds and precision stepping Abbreviations: bil. = bilateral; fNIRS = Functional Near-Infrared Spectroscopy; SMC = primary sensorimotor cortex; lat.…”
Section: Page 34 Of 57mentioning
confidence: 99%
See 1 more Smart Citation
“…Reflexive stabilization of eye and head as well as automatic locomotion at higher speed are mediated by infrathalamic brainstem and cerebellar locomotor centers [6466]. In contrast, conscious perception of body posture and motion, goal-directed movements, and control of low-speed locomotion are mediated by suprathalamic sensorimotor mechanisms and higher cognitive vestibular functions including spatial orientation and navigation [67,68].…”
Section: Discussionmentioning
confidence: 99%